The relationship between the Old Case Loads and New Case Loads in Nakivale refugee settlement in Southwestern Uganda - (:unkn) unknown (Journal of Eastern African Studies, 2016)
Forced migration from Rwanda has become a common trend. It has been there since time immemorial and is still continuing at varying magnitudes. Scholarly literature indicate that over 100,000 Rwandan refugees crossed into Uganda and other neighbouring countries of Burundi, Tanzania and Zaire (the present day Democratic Republic of Congo) in early 1960s seeking asylum following violent political and social changes in Rwanda that erupted in 1959. Rwanda was a former colony of Germany before the First World War which later came under the Belgian administration. It is comprised of three ethnic groups, Tutsi, Hutu and Twa, with the Hutu taking 85%, followed by the Tutsi at 14% and the Twa at 1% of the total population. Interestingly, they all speak the same language; Ikinyarwanda. Prior to colonization, the Tutsi, although smaller in number, were the ruling ethnic group over the majority Hutu. In 1959, as Rwanda was warming up to attain independence, tensions started erupting between the Tutsi and Hutu over who should rule the new country. It is believed that although the Tutsi were few in numbers, they were more elite and intelligent compared to the majority Hutu. The Hutu, having been mistreated and under looked during the reign of Tutsi, they were determined to supersede them this time round. As the tensions heightened, many Tutsi were killed and the remnants fled to neighbouring countries. To some scholars, this was blamed on the poor management by the Belgians who are believed to have dragged their feet at the beginning and later moved too fast without proper preparation for decolonization of the local communities. The Belgian colonial masters put in place identity cards that classified individual Rwandans as either Hutu or Tutsi which meant permanent racialised divisions in favour of the ruling Tutsi by then1.